Upper and Lower $τ^\starα(σ_1,σ_2)$-continuity (European Journal of Pure and Applied Mathematics, 2025)
A new class of continuous multifunctions between an ideal topological space and a bitopological space, called upper (lower) $τ^\starα(σ_1,σ_2)$-continuous multifunctions, has been defined and studied. Moreover, several characterizations and some properties concerning upper $τ^\starα(σ_1,σ_2)$-continuous multifunctions and lower $τ^\starα(σ_1,σ_2)$-continuous multifunctions are established.
Keywords: upper $τ^\starα(σ_1,σ_2)$-continuous multifunction; lower $τ^\starα(σ_1,σ_2)$-continuous multifunction